Enhancing indoor air quality: Assessing air purification technologies for effective pollution control - Daffa Arkananta Putra Yanni (Sanitasi: Jurnal Kesehatan Lingkungan, 2025)
Indoor air pollution poses serious health risks, highlighting the need for effective purification technologies. Advancements like high-efficiency particulate air (HEPA) filters and heating, ventilation, and air conditioning (HVAC) systems have been widely adopted while emerging methods such as photocatalytic oxidation (PCO), plasma-based systems, and smart air purifiers with real-time monitoring show great potential. This review evaluated the efficiency of these technologies in managing particulate matter (PM), volatile organic compounds (VOCs), and microbial contaminants. HEPA filters are highly efficient, capturing 99.97% of particles ≥0.3 microns. HVAC systems significantly reduce black carbon (BC) and PM concentrations by over 60%. Emerging technologies such as PCO and plasma-based systems demonstrate effectiveness in neutralizing VOCs and pathogens but raise concerns regarding byproducts like ozone. Smart purifiers provide enhanced pollutant monitoring and adaptive cleaning. The findings suggest that a hybrid approach, integrating traditional and advanced purification methods, can address a broader range of pollutants while ensuring cost-effectiveness and sustainability. Future research should focus on optimizing these technologies to minimize harmful byproducts, improve energy efficiency, and validate their real-world performance to support healthier indoor environments. These insights aim to guide the development of comprehensive strategies for pollution control in diverse settings.